A new endoscopic closure method for gastric mucosal defects: feasibility of endoscopic hand suturing in an ex vivo porcine model (with video) - Goto, Osamu; Sasaki, Motoki; Ishii, Hiroyuki; Horii, Joichiro; Uraoka, Toshio; Takeuchi, Hiroya; Kitagawa, Yuko; Yahagi, Naohisa (Endoscopy International Open, 2014)
Background and study aims: More secure endoscopic closure techniques for iatrogenic gastric defects are required for safe endoscopic surgery. We developed a novel endoscopic suturing method, endoscopic hand suturing (EHS), of gastric mucosal defects and determined its feasibility and efficacy ex vivo.Materials and methods: We created 24 mucosal defects (each 2 cm in diameter) by endoscopic submucosal dissection. The following three techniques were tested: EHS with a 3 – 0 barbed suture that was grasped with biopsy forceps (n = 6) or a prototype through-the-scope needle holder (n = 6) by endoscopy, looping with endoloops (n = 6) by endoscopy, and clipping with hemoclips (n = 6) by hand. The mucosal edges were attached to each other at three points. The closure strength was compared among the three groups, and the procedural duration was compared between the EHS and looping groups.Results: All 12 lesions were completely closed by EHS. The median strength of the closure, measured with a spring scale, was significantly greater in the EHS group (0.74 kg) than in the looping group (0.33 kg, P = 0.0012) or clipping group (0.07 kg, P = 0.0009). The median procedural duration did not significantly differ between the EHS and looping groups (19.7 vs. 19.8 minutes, P = 1.0000). The use of the needle holder significantly reduced the procedural duration compared with the biopsy forceps.Conclusion: Mucosal defects can be firmly closed with EHS, which may be helpful for establishing a safer and more secure endoscopic surgery.